A consensualidade e o processo administrativo disciplinar no Brasil - Condotta, Paula Thamyres (2023)
The present work aims to analyze the use of consensual means of conflict resolution within the administrative disciplinary process. With the adoption of the Democratic State of Law by the Constitution of 1988, the participation of the citizen in the administrative action means a democratic action that confers greater legitimacy in the administrative activity. With the express provision of the Principle of Administrative Efficiency, it demands a swift, effective and less expensive state action. In this context, consensuality presents itself as an alternative method to the imposing and unilateral action of the Administration, as a faster and less expensive instrument able to give effectiveness to administrative decisions, and, therefore, able to ensure the public interest. From this perspective, several legislations spread out regulating the possibility of using alternative means of conflict resolution with Public Administration as part. The Principle of Unavailability of the Public Interest and the Principle of Supremacy of the Public Interest were pointed out as arguments of resistance by the doctrine to the incorporation of consensual administrative action. In addition, with the advent of article 26 of the “LINDB” recognized as a general authorization for the celebration of commitments by the Public Administration weakens the obstacles once pointed out by the doctrine. In the scope of disciplinary sanctions, it cannot be different. In the scope of disciplinary sanctions, it cannot be different. The public servant plays a fundamental role in Public Administration, as the public servant acts on behalf of the Public Administration. The administrative disciplinary process is a state instrument to investigate administrative disciplinary infractions, whose nature is eminently sanctioning. However, in the light of the democratic precept and the principle of administrative efficiency, consensus must also be used as a disciplinary control mechanism, since it confers greater legitimacy to functional control, as it favors the participation of public servants in administrative decisions and proves to be a faster and less costly means of correction in prestige to administrative efficiency. he research was developed based on bibliographical and jurisprudential analysis. In the end, from the development of the research, it was possible to conclude that the coexistence of sanctioning action and consensual action in the scope of the disciplinary administrative process is possible